An optical MEMS accelerometer fabricated using double-sided deep reactive ion etching on silicon-on-insulator wafer. (19th April 2017) - Teo, Adrian J T; Li, Holden; Tan, Say Hwa; Yoon, Yong-Jin
Abstract: Optical MEMS devices provide fast detection, electromagnetic resilience and high sensitivity. Using this technology, an optical gratings based accelerometer design concept was developed for seismic motion detection purposes that provides miniaturization, high manufacturability, low costs and high sensitivity. Detailed in-house fabrication procedures of a double-sided deep reactive ion etching (DRIE) on a silicon-on-insulator (SOI) wafer for a micro opto electro mechanical system (MOEMS) device are presented and discussed. Experimental results obtained show that the conceptual device successfully captured motion similar to a commercial accelerometer with an average sensitivity of 13.6 mV G −1, and a highest recorded sensitivity of 44.1 mV G −1 . A noise level of 13.5 mV was detected due to experimental setup limitations. This is the first MOEMS accelerometer developed using double-sided DRIE on SOI wafer for the application of seismic motion detection, and is a breakthrough technology platform to open up options for lower cost MOEMS devices.